Author Correction: Human FCHO1 deficiency reveals role for clathrin-mediated endocytosis in development and function of T cells - Marcin Łyszkiewicz (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.